Sistem Aquaponik Budidaya Ikan Dalam Ember “Aquaponik Budikdamber” Sebagai Alternatif Keterbatasan Lahan - M. Yogi Riyantama Isjoni; Berliana Ifada; Hikmatul Nazila; Irnawan Syaputra; M. Aidil Ikhsan; Mifta Hurrahma; Nabilla Meilina Putri; Nurhakiki Inda Kumala Putri; Nopri Yastian; Rugeri Ramadhan; Tri Umbar Sari (Unri Conference Series: Community Engagement, 2021)
The Covid-19 pandemic that occurred in Indonesia in 2020 had an impact on aspects of life. One is the economic aspect. Mass layoffs occurred so that many people lost their jobs. So an alternative is needed that can help increase people's income during the pandemic, by utilizing the land around the house, and can be applied as a side business during the pandemic. Fish farming in buckets or known as Aquaponik Budikdamber, can be an alternative business in maintaining food security and increasing income during the pandemic. Aquaponik Budikdamber utilizes aquaponics techniques by raising fish while growing water spinach can minimize costs and is easy to implement. The Aquaponik Budikdamber socialization activity is one way to educate the community around Pematang Reba Village, Indragiri Hulu Regency. The fish used in Aquaponik Budikdamber are 60 catfish measuring 5-12 cm in an 80 L bucket. This program is carried out with the output of socialization activities on August 7, 2021, attended by 20 participants from residents of Pematang Reba Village, West Rengat District, Indragiri Regency Hulu, who was present in person at the socialization entitled "Fish Cultivation in Buckets (Aquaponik Budikdamber) Efforts to Maintain Food Security during a Pandemic". This activity makes the public educated about the practice of fish farming using narrow land, easy to do and cheap to maintain food security in the midst of the Covid-19 pandemic.